Abnormal liver function tests in the parenteral nutrition fed patient. Issue 2 (15th June 2010) - Gabe, S M; Culkin, A
Abstract : Liver dysfunction is common in individuals receiving parenteral nutrition (PN) and particularly in neonates and infants. Abnormalities of liver function tests in patients receiving short term PN are usually transient but in individuals receiving long term PN, substantial liver damage and ultimately end stage liver disease may occur. The aetiology is complex, involving a large number of patient related and nutrition related factors. The terminology intestinal failure associated liver disease (IFALD) is therefore more appropriate than PN associated liver disease. Effort should be made to prevent liver dysfunction by managing sepsis, avoiding parenteral overfeeding, employing cyclical parenteral feeding and encouraging enteral nutrition where possible. Intake of soybean based parenteral lipid emulsions should be reduced in individuals with established IFALD, possibly to be replaced by lipid emulsions containing medium chain triacylglycerol, monounsaturated fatty acids or fish oil although larger clinical studies are needed. Similarly, evidence supporting the widespread use of parenteral choline and taurine supplementation in the prevention or treatment of IFALD remains limited. There are more data to support the use of oral antibiotics to treat bacterial overgrowth and oral ursodeoxycholic acid in neonates. Ultimately, severe IFALD may necessitate referral for small intestine and/or liver transplantation.